The Influence of Financial Knowledge and Financial Attitudes on Financial Management Behavior: A Study of Food and Beverage Micro-Entrepreneurs in Sail District, Pekanbaru City - Liana Sesmitha, Echi; Ruzikna, Ruzikna (International Journal of Science, Technology & Management, 2023)
This study aims to determine whether financial knowledge influences financial management behavior, to determine whether financial attitudes affect financial management behavior, and to determine whether financial knowledge and financial attitudes influence financial management behavior. The research method used is quantitative method and uses secondary data and primary data. Primary data was obtained from respondents who were collected through a questionnaire consisting of 19 questions. The sample consisted of 76 respondents from a population of 314 business actors using the cluster sampling technique. The scale of measurement uses a Likert scale. Data analysis included: validity test, reliability test, multicollinearity test, heteroscedasticity test, normality test, multiple linear regression test, t test, f test, and test of the coefficient of determination. The data analysis technique of this research uses SPSS. The findings of this study show that (1) financial knowledge has a significant influence on financial management behavior in micro business actors in Sail District, (2) financial attitudes have a significant influence on financial management behavior in micro business actors in Sail District, and (3) financial knowledge and financial attitudes have a significant influence on financial management behavior in micro business actors in Sail District.